Value of quantitative and qualitative analyses of serum and urine cell-free DNA as diagnostic tools for bladder cancer: a meta-analysis. Issue 7 (3rd July 2019) - Cao, Zhangjun; Peng, Longfei; He, Ke; Wang, Xin; Lu, Youlu; Zhang, Ying; Bi, Liangkuan
ABSTRACT: Background : Qualitative and quantitative analysis of circulating cell-free DNA (cfDNA) is a potential detection method for bladder cancer. Many studies have focused on the reliability of these results, but the conclusions have not been consistent. Methods : We performed a diagnostic meta-analysis to investigate the diagnostic significance of serum and urine cfDNAs with tumor tissues as the standard control. We searched the MEDLINE, EMABASE, and Cochrane Central Controlled Trials Register (CCTR) databases until January 2019. Results : A total of 11 studies involving early and/or advanced bladder cancer were finally included. The overall diagnostic accuracy was measured as follows: pooled sensitivity and specifcity were 0.69 (95%CI: 0.67, 0.71) and 0.72 (95%CI: 0.70, 0.74). Pooled positive likelihood ratio and negative likelihood ratio were 3.10 (95%CI: 2.35, 4.07) and 0.41 (95%CI: 0.34, 0.49). Combined diagnostic odds ratio was 8.26 (95%CI: 5.64, 12.11). A high diagnostic accuracy was demonstrated by the summary receiver operating characteristic curve, with area under the curve of 0.80 (95%CI: 0.77, 0.83). Conclusions : CfDNA assay has high diagnostic value for the detection of bladder cancer. Larger sample studies are needed to further confirm our conclusions and to make this approach more sensitive and specific.